Sex-Related Differences in Outcomes After Endovascular Treatment of Patients With Late-Window Stroke. Issue 2 (5th January 2022) - Bala, Fouzi; Casetta, Ilaria; Nannoni, Stefania; Herlihy, Darragh; Goyal, Mayank; Fainardi, Enrico; Michel, Patrik; Thornton, John; Power, Sarah; Saia, Valentina; Hegarty, Aidan; Pracucci, Giovanni; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Sex-related differences exist in many aspects of acute stroke and were mainly investigated in the early time window with conflicting results. However, data regarding sex disparities in late presenters are scarce. Therefore, we sought to investigate differences in outcomes between women and men treated with endovascular treatment in the late time window. Methods: Analyses were based on the SOLSTICE Consortium (Selection of Late-Window Stroke for Thrombectomy by Imaging Collateral Extent), which was an individual-patient level analysis of seven trials and registries. Baseline characteristics, 90-day functional independence (modified Rankin Scale score ≤2), mortality, and symptomatic intracranial hemorrhage were compared between women and men. Effect of sex on the association of age and successful reperfusion (final Thrombolysis in Cerebral Infarction 2b–3) with outcomes was assessed using multivariable logistic regression adjusted for age, National Institutes of Health Stroke Scale score, Alberta Stroke Program Early CT Score, time from onset to puncture, occlusion location, intravenous thrombolysis, and successful reperfusion, with interaction terms. Results: Among 608 patients treated with endovascular treatment, 50.5% were women. Women were older than men (median age of 72 versus 68 years, P =0.02) and had a lower prevalence of tandem occlusions (14.0% versus 22.9%, P =0.005). Workflow times were similar between sexes. Adjusted outcomes did not differ between women and men. Functional independence at 90 days was achieved by 127 out of 292 women (43.5%) and 135 out of 291 men (46.4%). Mortality at 90 days (54 [18.5%] versus 48 [16.5%]) and symptomatic intracranial hemorrhage (37 [13.3%] versus 33 [11.6%]) were similar between women and men. There was no sex-by-age interaction on functional outcomes. However, men had higher likelihood of mortality ( P interaction =0.003) and symptomatic intracranial hemorrhage ( P interaction =0.017) with advancing age. Sex did not influence the relation between successful reperfusion and outcomes. Conclusions: In this multicenter analysis of late patients treated with endovascular treatment, sex was not associated with functional outcome. However, sex influenced the association between age and safety outcomes, with men experiencing worse outcomes with advancing age.